Dampak Kebijakan Pemerintah Daerah dalam Pengelolaan PKL di Kota Jakarta, Bandung dan Surabaya - Murtanti Jani Rahayu; Septyani Widyastuti (TATALOKA, 2021)
As a developing country, Indonesia has a huge number of street vendors. Because of that, the existence of street vendors needs a special attention. This special attention is needed because streer vendors mostly occupy city's public spaces. Street vendor management in Indonesia's cities is based on the regulations that was made by each regional government which is pointing to Indonesia's higher level of regulation. Each regional regulation has their own unique characteristics. Jakarta, Bandung, and Surabaya are big cities that have street vendor problems that also have street vendor management regulations. From those three cities, the advantages and disadvantages of their regulation's contents will be revealed, enriched by information digging and research results. From the regulation side, those three cities showed their concern about regulations regarding street vendors. The forms of restructuring that has been done are relocation and stabilization. Those three cities are also supported by private sector regarding street vendor management. Street vendor management has a vital contribution towards regional economical growth and street vendor's income growth. These positive impacts increases the efficiency of city space management, so the city itself will look tidy, beautiful, and not congested, but street vendors are still poppimg out in restricted areas and old spaces, if the new managed locations are far from the crowds, the impact will decrease street vendor's income